Pengembangan Web Admin Aplikasi Pulsa Dengan Reactjs Menggunkan metode Rapid Application Development - Dermawan, Muhammad Dery; Suroyo, Heri; Wijaya, Alek; ., Jemakmun (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Credit has developed into a basic social need in the digital era, therefore a tool is needed that can help in delivering this service. The credit admin application, which is a web-based application that can be accessed from anywhere, can be a solution in offering this service and by using the Xendit payment gateway, users can make payments flexibly, making it easier to make transactions on the application. A software development strategy known as Rapid Application Development is used in this research to create applications. By focusing on fast turnaround times and adaptability to change, this method can speed up the development process. Test findings carried out for this research include API testing and test cases. API test results include tests using the get, post, and put methods. In the user menu the get API method has an average time of 6.8ms and uses 294 B of memory, then in the post method it takes an average of 1630ms or 1.6 seconds and uses 294 B of memory, and in the put method it takes an average of 27. 5ms and uses 298 B memory. Then, in testing the test case for the application, all tests on each feature were successful